PENILAIAN RESIKO KEJAHATAN ILLEGAL CONTENT MENGGUNAKAN FRAMEWORK NIST 800-30 - Ahmad Marsehan; Muhhamad Izman Herdiansyah; Ahmad Haidar Mirza; Darius Antoni (Paradigma, 2020)
In the current era, information dissemination tends to be easier to do, this is due to the development of the internet and smartphone technology, which causes everyone to act as a sender and receiver of news without having to be filtered. This will certainly lead to new problems, especially potential violations of the law or criminal acts of the ITE Law such as illegal content. To overcome this, it is necessary to apply cyber-risk management so that cyber risks in the aspect of illegal content can be managed. Based on research conducted using the NIST 800-30 Framework on several students in Lubuklinggau City, the behavior or actions that are usually carried out related to handling the dissemination of information on social media or the internet are in the aspect of not understanding differences in information containing illegal content and lack of understanding of legal consequences. in disseminating illegal content information on social media it is included in the high risk category, furthermore the inability of the public to assess the reliability and pleasure of sharing information without knowing the information's credibility falls into the medium risk category, and finally students are happy to read controversial information even though the information is not clearly its credibility is included in the low risk category.